Who we are Asians (Gale virtual reference library, 2016)
Provides detailed estimates of the numbers of Asians nationally and by state and metropolitan area. Also includes the latest socioeconomic data on the Asian population. Provides detailed spending data for Asian households. Results from the American Time Use Survey are also presented, profiling Asian time use and comparing it to the averages.